Role of PCSK9 in Homocysteine-Accelerated Lipid Accumulation in Macrophages and Atherosclerosis in ApoE−/− Mice - Jin, Ping; Gao, Dengfeng; Cong, Guangzhi; Yan, Ru; Jia, Shaobin (Frontiers in Cardiovascular Medicine, 2021)
Background: Homocysteine(Hcy) has been established as an independent risk factor for atherosclerosis, and the involvement of hyperhomocysteinemia(HHcy) in atherosclerotic lesions is complex. Proprotein convertase subtilisin kexin 9(PCSK9) has vital importance in lipid metabolism, and its inhibitors have intense lipid-lowering and anti-atherosclerotic effects. However, the underlying effect of PCSK9 on HHcy-accelerated dyslipidemia of macrophages is still uncertain. The purpose of this study was to investigate the potential role of PCSK9 in Hcy-induced lipid accumulation and atherosclerotic lesions. Methods: In vitro, gene and protein expressions were assessed by real-time quantitative PCR and western blot in THP-1 macrophages with Hcy incubation. Lipid accumulation and cholesterol efflux were evaluated with Hcy treatment. SBC-115076 was used to examine the role of PCSK9 in ATP-binding cassette transporter A1 and G1(ABCA1 and ABCG1)-dependent cholesterol efflux. In vivo, lesion area, lipid deposition and collagen contents were determined in aortas of ApoE-/- mice under a methionine diet. SBC-115076 was subcutaneously injected to explore the potential effects of PCSK9 inhibition on alleviating the severity of HHcy-related atherosclerotic lesions. Results: In THP-1 macrophages, Hcy dose- and time-dependently promoted PCSK9 gene and protein levels without regulating the translation of Low-density lipoprotein receptor(LDLR). SBC-115076 used to inhibit PCSK9 largely alleviated lipid accumulation and reversed the cholesterol efflux to apolipoprotein-I(apoA-I) and high-density lipoprotein(HDL) mediated by ABCA1 and ABCG1. In ApoE-/- mice, methionine diet induced HHcy caused larger lesion area and more lipid accumulation in aortic roots. SBC-115076 reduced atherosclerotic severity by reducing the lesion area and lipid accumulation and increasing expressions of ABCA1 and ABCG1 in macrophages from atherosclerotic plaque. In addition, SBC-115076 decreased plasma Hcy level and lipid profiles significantly. Conclusion: PCSK9 promoted lipid accumulation via inhibiting cholesterol efflux mediated by ABCA1 and ABCG1 from macrophages and accelerated atherosclerotic lesions under HHcy treatment. Inhibiting PCSK9 may have anti-atherogenic properties in HHcy-accelerated atherosclerosis.